PENGARUH PENGETAHUAN PERPAJAKAN, KETEGASAN SANKSI PERPAJAKAN DAN KEADILAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Mu'arif, Syamsul; Lestari, Suci (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
The purpose of this research is to analyze of tax knowledge, firmness of tax sanction, and tax fairness on taxpayer compliance SMEs in Kecamatan Tajur Halang, Kabupaten Bogor. Sampling ini this research used random sampling and obtained 77 sampels of SMEs. The data anayisis method is quantitative data analysis, using primary data by giving questionnaries to SMEs and using SPSS version 28 computer program tools. The result of this research partially show that the tax knowlegde and firmness of tax sanction have an effect on taxpayaer compliance SMEs, tax fairness has no effect on taxpayaer compliance SMEs. Meanwhile simulaneously, tax knowlegde, firmness of tax sanction, and tax fairness have an effect on taxpayaer compliance with 327 populations and 77 samples are obtained with an R2 contribution of 52%, while 48% is influenced by other variiables noot exmined in this study